FERTILITY PRESERVATION IN ENDOMETRIAL CANCER PATIENTS: OPTIONS, CHALLENGES AND PERSPECTIVES - Terzic, Milan; Norton, Melanie; Terzic, Sanja; Bapayeva, Gauri; Aimagambetova, Gulzhanat (Ecancermedicalscience, 2020)
Several different approaches have been designed by physicians in order to preserve fertility in younger patients with endometrial carcinoma. There are various options offering different advantages, but hysteroscopic resection of pathologic endometrial tissue with placement of a Levonorgestrel Intrauterine Device has proven to be the most successful in allowing patients to conceive and give birth afterwards. However, conservative treatments should only be considered in patients with low-grade and low-stage endometrial tumours. There are many published studies which have sought out a preferable approach to treating endometrial cancer whilst preserving fertility. However, more research on this matter is needed to allow a better understanding as to which techniques/approaches are optimal. In this review, we will summarise the current available treatment options for endometrial cancer in patients of reproductive age.
Keywords: Type of access: Open Access; endometrial cancer; fertility preservation; conservative management intrauterine system; IUD; hysteroscopy